Scope of Islamic Business Economics Fiqh: Analysis of Research Trends Through Bibliometrics and Systematic Literature Review - Sari, Junia Mayang; Wira, Ahmad; Duhriah, Duhriah (Jurnal Iqtisaduna, 2025)
This study aims to identify trends in the field of Islamic business economics fiqh. This study uses bibliometric methods and systematic literature review (SLR) to obtain a broader and deeper picture of the development of Islamic business economics fiqh studies and research trends in developing these studies. In this case, the literature collected comes from the Scopus database using Publish or Perish and Scopus.com software. The results show that the trend of Islamic business economics studies is increasing and this research has become a favorite among researchers related to the topic of Islamic economic and business fiqh. The results of Vosviewer mapping and selected journal reviews show that the future scope of Islamic economics studies is based on publication trends in the development of Islamic financial systems, economic factors, the development of sharia insurance, and contemporary Islamic business economics practices.